PENGARUH KEPEMIMPINAN, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA PERANGKAT DESA DENGAN DISIPLIN KERJA SEBAGAI VARIABLE INTERVENING ( STUDI KASUS DESA CERMEE, DESA SULING WETAN, DESA SULING KULON ) - Agnes, Sofia; Karnadi, Karnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Village office is a building or room used as the center for administrative functions at the village level. This place serves as a meeting point for village government officials, including the village head, village administrative staff, and various departments or units related to public services and the interests of the village community. This research aims to analyze the factors that influence the performance of village officials with work discipline as an intervening variable (a case study in Cermee Village, Suling Wetan Village, Suling Kulon Village). The population for this study consists of all village officials from cermee village, suling wetan village, and suling kulon village, totaling 49 individuals. The sampling technique used is nonprobability sampling. Data analysis and hypothesis testing in this study used Partial Least Squares (PLS) 3.0. The results show that Leadership has a significant positive influence on work discipline, Motivation has a significant positive influence on work discipline, Organizational culture has a significant positive influence on work discipline, Leadership has a significant negative influence on performance, Motivation has a significant negative influence on performance, Organizational culture has a negative but not significant influence on performance, Work discipline has a significant positive influence on performance, Leadership has a significant positive influence on performance through work discipline, Motivation has a significant positive influence on performance through work discipline, and Organizational culture has a negative but not significant influence on performance through work discipline.